Taking the green pill: Macro-financial transition risks and policy challenges in the MATRIX model - Emanuele Ciola; Enrico Turco; Massimiliano Rizzati; Davide Bazzana; Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2024)
This paper evaluates the macroeconomic and financial risks of the energy transition using an extended MATRIX model, a multi-agent, multi-sector integrated assessment framework for the Euro Area. The model features endogenous, directed technical change in the energy sector and a decentralized electricity market based on merit-order rule. Energy firms switch technologies based on relative profitability, capturing feedback loops between R&D, productivity gains, and competitiveness, which may lead to either brown lock-in or green energy transition. We compare conventional policies - brown tax (BT), unconditional green subsidy (GS), and conditional green subsidy (CGS) linked to R&D - with alternative policy mixes, such as coordinated monetary policy, green finance and green industrial policy. Results show that while conventional policies modestly increase transition likelihood, they entail GDP losses due to production and financial constraints. These can be mitigated with green industrial policy and green finance, which alleviate sectoral bottlenecks and foster a more effective transition.
Keywords: C63; E61; O33; Q43; Q55; 330; Energy Sector; Agent-Based Models; Macroeconomic Dynamics; Directed Technological Change; Green Transition